A Stable Homoleptic Organometallic Iron(IV) Complex. Issue 56 (11th September 2020) - Prakash, Om; Chábera, Pavel; Rosemann, Nils W.; Huang, Ping; Häggström, Lennart; Ericsson, Tore; Strand, Daniel; Persson, Petter; Bendix, Jesper; Lomoth, Reiner; Wärnmark, Kenneth
Abstract: A homoleptic organometallic Fe IV complex that is stable in both solution and in the solid state at ambient conditions has been synthesized and isolated as [Fe(phtmeimb)2 ](PF6 )2 (phtmeimb=[phenyl(tris(3‐methylimidazolin‐2‐ylidene))borate] − ). This Fe IV N‐heterocyclic carbene (NHC) complex was characterized by 1 H NMR, HR‐MS, elemental analysis, scXRD analysis, electrochemistry, Mößbauer spectroscopy, and magnetic susceptibility. The two latter techniques unequivocally demonstrate that [Fe(phtmeimb)2 ](PF6 )2 is a triplet Fe IV low‐spin S= 1 complex in the ground state, in agreement with quantum chemical calculations. The electronic absorption spectrum of [Fe(phtmeimb)2 ](PF6 )2 in acetonitrile shows an intense absorption band in the red and near IR, due to LMCT (ligand‐to‐metal charge transfer) excitation. For the first time the excited state dynamics of a Fe IV complex was studied and revealed a ≈0.8 ps lifetime of the 3 LMCT excited state of [Fe(phtmeimb)2 ](PF6 )2 in acetonitrile. Abstract : A stable homoleptic organometallic Fe IV complex, [Fe(phtmeimb)2 ](PF6 )2 was synthesized and isolated. It is stable in the solid state and in acetonitrile at ambient temperature. The excited state of the 3 GS [Fe(phtmeimb)2 ](PF6 )2 was shown to be of 3 LMCT nature, and shows a 0.8 ps lifetime as determined by transient absorption spectroscopy.